Ukotveni v pohybu: reflexivní identita mladých dobrovolníků - Hrubeš, Ondřej (Lidé města, 2024)
This paper combines the framework of collective and reflexive volunteering with emerging adulthood theory in order to investigate volunteer work in communities as a source of reflexive identity. In the theoretical part, it looks into the concept of identity from the reflexive modernization perspective, volunteer communities, and emerging adulthood. The empirical part is based on qualitative biographical research with an emphasis on the position of sociological romanticism. It analyzes six biographical interviews with young adult volunteers and with one focus group that four of them were involved in. The outcomes indicate that volunteers in the age of emerging adulthood incline to communities and to shared identity, no matter how their life situation pushes them to reflexive behavioural patterns. After reviewing their life course as a set of important milestones, they interpret their volunteer and community experience as a biographically passing but indispensable chapter in life. This experience persists in their personal identity in the sense of a fixed point that can help them choose their next path in life.